Respuesta :
Answer:
[tex]\large\boxed{-10x^6+5x^5+15x^4-10x^3-6x^2}[/tex]
Step-by-step explanation:
[tex](5x^5+4x^2-2x^6+6x^4)-(10x^2+10x^3+8x^6-9x^4)\\\\=5x^5+4x^2-2x^6+6x^4-10x^2-10x^3-8x^6-(-9x^4)\\\\=5x^5+4x^2-2x^6+6x^4-10x^2-10x^3-8x^6+9x^4\\\\\text{combine like terms}\\\\=(-2x^6-8x^6)+5x^5+(6x^4+9x^4)-10x^3+(4x^2-10x^2)\\\\=-10x^6+5x^5+15x^4-10x^3-6x^2[/tex]
Answer:
-10x^6+5x^5+15x^4-10x^3-6x^2.
Step.by-step explanation:
5x^5+4x^2-2x^6+6x^4 - (10x^2+10x^3+8x^6-9x^4).
First distribute the negative over the parentheses:
=5x^5+4x^2-2x^6+6x^4 - 10x^2-10x^3-8x^6+9x^4
Now bring like terms together:
= -2x^6-8x^6+5x^5+6x^4+9x^4-10x^3+4x^2-10x^2
= -10x^6+5x^5+ 15x^4-10x^3-6x^2.